Pemberdayaan Masyarakat Melalui Pengembangan Budidaya Ikan Lele Teknologi Bioflok di Kelurahan Pinang Jaya, Bandar Lampung, Lampung - Hudaidah, Siti; Yusup, Maulid Wahid (Lembaga Penelitian dan Pengabdian Universitas Lampung, 2017)
Abstract — Pinang Jaya is one of urban village area in Bandar Lampung which is potential for aquaculture development. Community development throught catfish culture based biofloc tecnology in this urban village has been done for 6 month from july-desember 2016. This activity aimed to improve the community skill especially catfish culture based biofloc tecnology. Methods used in this activity was training and empowering. The community was trained about cycle pond contruction and fish culture based biofloc tecnology tecnique. The community participated was 20 people. Supporting scheme in this program was four cycle pond size diameter 2 m, including fish larvae (seed), feed and house of cultured. There were two principal approacheshas been done to empower the catfish culture based biofloc tecnology which were technical ana participate approach. Based on the training and empowering results, this activity managed to improve knowledge of fish culture in Pinang Jaya from 24% to 90%. Fish farm had ability to culture the catfish based biofloc technology. Keywords — biofloc, catfish, training, community empowerment.